1986
DOI: 10.1128/jb.168.3.1265-1271.1986
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and sequence of the gene for ferredoxin I from the cyanobacterium Anabaena sp. strain PCC 7120

Abstract: The structural gene for ferredoxin I, petF, from the cyanobacterium Anabaena sp. strain PCC 7120 has been isolated from a recombinant lambda library. Mixtures of tetradecanucleotides and heptadecanucleotides, each containing all possible DNA sequences corresponding to two separate regions of the ferredoxin amino acid sequence, were synthesized and used as hybridization probes to identify a genomic clone containing the coding sequence for the petF gene. The sequence of the entire petF coding region and portions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(56 citation statements)
references
References 44 publications
0
56
0
Order By: Relevance
“…6). S1 nuclease mapping with a probe that included the 5' end of atpI, all of gene 1, and 500 bp 5' to gene 1 (Fig. 1, probe 1) confirmed the single mRNA endpoint identified in the primer extension assay and demonstrated that no additional RNA endpoints map between gene 1 and atpl (data not shown).…”
Section: Resultsmentioning
confidence: 77%
“…6). S1 nuclease mapping with a probe that included the 5' end of atpI, all of gene 1, and 500 bp 5' to gene 1 (Fig. 1, probe 1) confirmed the single mRNA endpoint identified in the primer extension assay and demonstrated that no additional RNA endpoints map between gene 1 and atpl (data not shown).…”
Section: Resultsmentioning
confidence: 77%
“…The 5Ј ends of the pta and ack mRNAs were mapped with the following oligonucleotides: pta1 (5Ј-GTTAAGTTTCTTTGCTCTTTCACT-3Ј, nucleotides 52 to 75 relative to the identified transcriptional start site of pta), pta2 (5Ј-CAAGGATCTTGGCAGCTGCCTG-3Ј, nucleotides 118 to 139), ack1 (5Ј-CCTATCCTCTCGCAAAGACCTAC-3Ј, nucleotides 1215 to 1237), and ack2 (5Ј-CCAGTACTTTCATGTGTAAACC-3Ј, nucleotides 1125 to 1146). Primer extension analysis was based on a procedure described by Alam et al (2). Briefly, RNA (10 to 20 g) isolated from acetate-grown M. thermophila cells was pelleted and the pellet was resuspended in a solution consisting of 2 mol of primer and 7.5 M (each) dGTP, dCTP, and dTTP.…”
Section: Methodsmentioning
confidence: 99%
“…The 5' ends of the fdxA-and ORFl-specific mRNAs were mapped as described before (3) except that [a-35S]dATP (1,000 to 1,500 Ci/mmol) was substituted for [a-32P]dATP. The 21-mer oligonucleotide probes II (complementary to nucleotides +85 to +105 offdxA; see ORFl-specific primers (15 ng) were annealed to 10 or 25 ,ug, respectively, of total M. thermophila RNA which had been treated with DNase.…”
Section: Methodsmentioning
confidence: 99%